Simulakra Akuntan (si) Di Tengah Hiperealitas Revolusi Industri 4.0 - Luky Patricia Widianingsih (Departement of Mathematics Education, 2024)
This article offers an idea of imagination looking at the reality of accounting science and the practice of accountants in the middle of the background of the Industrial Revolution 4.0 (IR 4.0) where the world of simulacra and simulation applies. Baudrillard's thinking is used as an eyeglass in looking at the reality of IR 4.0 to obtain a picture of possible movements that occur in the role of accountant(ing) in generating the reality of company performance. The four stages of the simulacra process are used to see the possible shifts that occur in the reality of financial reporting during hyper-reality challenges. Hyper-reality, simulacra, and simulation thinking as critical analysis tools for the presence of IR 4.0 bring to self-awareness that reality can be formed. The accounting process and output should not only be a value of symbol signs and values, but something also that is false and does not show the truth.